Antibacterial activity of six medicinal Cameroonian plants against Gram-positive and Gram-negative multidrug resistant phenotypes. Issue 1 (December 2016) - Voukeng, Igor; Beng, Veronique; Kuete, Victor
Abstract Background Infectious diseases due to multidrug-resistant bacteria are one of the causes of treatment failures contributing to an increase in mortality and/or morbidity. In this study, we evaluated the antibacterial potential of different parts of six medicinal plants namelyAlstonia boonei, Ageratum conyzoides, Croton macrostachys, Cassia obtusifolia, Catharanthus roseus andPaullinia pinnata against a panel of 36 multi-drug resistant (MDR) Gram-negative and Gram-positive bacteria. Methods Minimum Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) of the methanol extracts from different parts of the plants were determined using broth microdilution method; standard phytochemical methods were used for phytochemical screening. Results Several phytochemical classes such as polyphenols, sterols, triterpenes, alkaloids, flavonoids and saponins were identified in the plant extracts. MIC values obtained ranged from 64 to 1024 μg/mL. Leaves extract ofCatharanthus roseus (86.11 %), Croton macrostachys (83.33 %) andPaullinia pinnata (80.55 %) displayed the best antibacterial spectra. The lowest MIC value of 64 μg/mL was obtained with thePaullinia pinnata stems extract andCassia obtusifolia extract against the strain ofStaphylococcus aureus MRSA8. Results also showed that the tested samples generally displayed bacteriostatic effects with MBC values obtained in only 3.35 % of the cases where plant extracts were active. Conclusion The results obtained at the end of this study demonstrate for the first time the antibacterial activity of the studied medicinal plants against MDR bacteria. The tested plants could be a reservoir of molecules to fight against MDR bacterial infections.